2016
DOI: 10.1002/14651858.cd010246.pub2
|View full text |Cite
|
Sign up to set email alerts
|

School-based education programmes for the prevention of unintentional injuries in children and young people

Abstract: School-based education programmes for the prevention of unintentional injuries in children and young people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 212 publications
2
35
0
Order By: Relevance
“…Of the 18 Cochrane reviews that reported using a citation index to conduct citation searching, 15 (83%) reported the name of the citation index(es) used. Google Scholar was reported in one review 55 ; Scopus was reported in two reviews 24,29 ; and Web of Science was reported in 13 reviews, [26][27][28][29]31,32,[34][35][36][37][38][39][40] including seven reviews [26][27][28][29]32,34,39 that reported searching the Science Citation Index (a subset of the Web of Science) in particular and one review 35 that reported searching the Core Collection (which includes the Social Sciences Citation Index and Arts & Humanities Citation Index) in particular.…”
Section: What Citation Indexes Are Used and How Frequently?mentioning
confidence: 99%
“…Of the 18 Cochrane reviews that reported using a citation index to conduct citation searching, 15 (83%) reported the name of the citation index(es) used. Google Scholar was reported in one review 55 ; Scopus was reported in two reviews 24,29 ; and Web of Science was reported in 13 reviews, [26][27][28][29]31,32,[34][35][36][37][38][39][40] including seven reviews [26][27][28][29]32,34,39 that reported searching the Science Citation Index (a subset of the Web of Science) in particular and one review 35 that reported searching the Core Collection (which includes the Social Sciences Citation Index and Arts & Humanities Citation Index) in particular.…”
Section: What Citation Indexes Are Used and How Frequently?mentioning
confidence: 99%
“…We also highlight the importance of unintentional injury interventions, legislation, and enforcement at a national level [21]. According to the characteristics of injuries in different age groups, the government can implement targeted interventions in different crowds and then test the effectiveness of them [34]. For instance, to protect children from fall-related injuries, schools can install soft rubber and waterproof oor for schoolyards [35].…”
Section: Suggestions To Decision-makersmentioning
confidence: 99%
“…We also highlight the importance of unintentional injury interventions, legislation, and enforcement at a national level [21]. According to the characteristics of injuries in different age groups, the government can implement targeted interventions in different crowds and then test the effectiveness of them [34]. For instance, to protect children from fall-related injuries, schools can install soft rubber and waterproof floor for schoolyards [35].…”
Section: Suggestions To Decision-makersmentioning
confidence: 99%